2023
DOI: 10.1002/hpm.3629
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hospital emergency department visits accurately: A systematic review

Abstract: Objectives The emergency department (ED) is a very important healthcare entrance point, known for its challenging organisation and management due to demand unpredictability. An accurate forecast system of ED visits is crucial to the implementation of better management strategies that optimise resources utilization, reduce costs and improve public confidence. The aim of this review is to investigate the different factors that affect the ED visits forecasting outcomes, in particular the predictive variables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…The FE approach employed in this study created a set of new predictor variables based on arrival timestamps. A recent systematic review on ED arrival forecasting [76] suggests, for future studies, that exploring new variables with potential to become significant and reliable predictors is an underexplored area, requiring further research. Our study addresses this demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FE approach employed in this study created a set of new predictor variables based on arrival timestamps. A recent systematic review on ED arrival forecasting [76] suggests, for future studies, that exploring new variables with potential to become significant and reliable predictors is an underexplored area, requiring further research. Our study addresses this demand.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the models presented in Table A3 In Section 2, we demonstrated that the most commonly used metrics for evaluating patient arrival predictions are MAPE and RMSE. Both metrics enable direct comparison since they are scale-independent, allowing for the assessment of predictions across different scenarios [71], [76]. MAPE presents results in percentage form, which is more easily interpretable [51].…”
Section: Overview Of Selected Machine Learning Algorithms and Perform...mentioning
confidence: 99%
“…In 2013, Wallace et al [ 6 ] presented a systematic review of the probability of repeat admission in community-dwelling adults, and in 2014, Wallace et al [ 7 ] presented a systematic review of risk prediction models to predict emergency hospital admission in community-dwelling adults. In the most recent years (2021, 2022 and 2023), several systematic reviews have been presented on prediction models for admissions [ 8 , 9 , 10 , 11 , 12 ]. Hence, there are multiple studies focused on predicting patients’ risk scores when admitted to the ED or hospital.…”
Section: Introductionmentioning
confidence: 99%
“…AutoCAD, which was initially introduced in 1982, quickly gained widespread usage among architects and designers due to its ability to enhance the efficiency of the design and drafting procedures. The initial computer-aided design and drafting (CADD) systems played a pivotal role in advancing the process of digitising design methodologies [10]- [13].…”
Section: Introductionmentioning
confidence: 99%